Factors Affecting the Quality of Life of Diabetes Mellitus Patients - Masithoh, Robiul Fitri (International Journal of Health Sciences, 2025)
Background:Diabetes Mellitus (DM) is a chronic disease that impacts not only the physical but also the psychological and social well-being of sufferers. The quality of life of DM patients is influenced by various internal and external factors, requiring a comprehensive understanding for management. Objective:This study aims to analyze the factors that influence the quality of life of type 2 Diabetes Mellitus patients. Method:The study used a descriptive analytical design with a cross-sectional approach in 120 type 2 DM patients undergoing treatment at Community Health Centers and hospitals in City X. The instruments used included the WHOQOL-BREF, MSPSS, and MAQ questionnaires, as well as clinical data from medical records. Data analysis was performed using multiple linear regression tests. Results:The results showed that education level (p=0.01), social support (p<0.01), medication adherence (p=0.03), and fasting blood sugar levels (p=0.02) significantly influenced the quality of life of DM patients. Age, gender, and duration of DM did not have a significant effect. Conclusion:The quality of life of DM patients is primarily influenced by psychosocial and behavioral factors. Interventions that emphasize education, strengthening social support, and improving medication adherence are needed to achieve a better quality of life.